Antitumor effects of naturally occurring oligomeric resveratrol derivatives. Issue 11 (7th August 2013) - Qiao, Haishi; Chen, Xiaoqing; Xu, Lanfang; Wang, Jingjing; Zhao, Guoyan; Hou, Yayi; Ge, Hui Ming; Tan, Ren‐Xiang; Li, Erguang
Abstract : This study was designed to evaluate and characterize the molecular basis of antitumor activity of naturally occurring resveratrol (RES; 3, 5, 4 ′ ‐trihydroxy‐ trans ‐stilbene) derivatives. The compounds were isolated from plants in previous studies and characterized spectroscopically. The antitumor activities of 31 RES derivatives, including dimers, trimers, and tetramers of RES, were evaluated using cell‐based assays and validated on a murine model. Several trimeric and a tetrameric stilbenoids induced tumor cell apoptosis or growth arrest of several tumor cell lines with IC50 values (2.8–19.7 μM), significantly lower than that of RES (IC50 >70 μM). Using pauciflorol B (PauB) as an example, we showed that the compound induced apoptosis p53 dependently, inducing p53 accumulation and p53‐modulated gene expression in cells with wild‐type p53, but not in those with nonfunctional p53. Reexpression of p53 in p53‐null cells rescued cell death response. In parallel, the MAPK/p38 was activated and critical for PauB‐induced killing. Interestingly, activation of p38 in p53 deficient cells was sufficient to drive cells into senescence via the p16–pRb pathway. Finally, PauB dose‐dependently inhibited tumor growth on nude mice. Naturally occurring trimeric and tetrameric stilbenoids are potent antitumor agents. Those compounds exert antitumor effect through p53‐dependent induction of apoptosis or senescence.—Qiao, H., Chen, X., Xu, L., Wang, J., Zhao, G., Hou, Y., Ge, H. M., Tan, R‐X., Li, E. Antitumor effects of naturally occurring oligomeric resveratrol derivatives. FASEB J . 27, 4561–4571 (2013). www.fasebj.org